Performance Analysis of Zakat-Based Empowerment to Improve Mustahik's Welfare - Maulidia, Rina; Imam Mukhlis (Open Access Indonesia Journal of Social Sciences, 2022)
This study aims to analyze the performance of zakat in improving the welfare of mustahik through zakat-based empowerment programs. Mustahik's welfare can be measured in terms of material and spiritual conditions, level of human development, and level of independence of mustahik. This research is a quantitative study using a multi-stage weigh index estimation technique that functions to generate a zakat welfare index from each variable. The data used are primary and secondary data, primary data obtained from interviews, and distributing questionnaires to zakat recipients of Rumah Zakat in Malang. While the secondary data was obtained from the results of the literature study. The sampling technique used was purposive sampling to obtain data following the research objectives. The results of this study are, first, the results found that zakat can improve the material and spiritual conditions of mustahik. Based on the CIBEST model, it has been found that there is an increase in the welfare index of mustahik by 42.5%. Second, zakat-based empowerment increases the condition of the mustahik HDI by 3.1%, which means that zakat has not been able to have a major influence on the mustahik HDI. Third, the zakat-based empowerment program can increase the mustahik's level of independence by 16.8%. This index shows that mustahik already has a permanent job or business and saves after obtaining empowerment. Based on the research that has been done, it can be concluded that zakat-based empowerment can improve the welfare of mustahik. It is noted that the welfare of mustahik has increased by 21.6% from the previous condition.